Binge Drinking at the University of Wisconsin--Eau Claire - Engum, Rylee R.; Klasek, Samantha N.; Fernandez, Lucia Weg; Johnson, Paula M. (My University, 2013)
The Centers for Disease Control and Prevention (CDC) defines binge drinking as 5 or more drinks in about 2 hours for males or 4 or more drinks for females. The CDC found that in 2010 Wisconsin led the nation in prevalence and intensity of binge drinking (percent of adults binge drinking and number of drinks when bingeing, respectively) (CDC, 2012). Also, 18-24 year olds were the age group with the highest rate of binge drinking. The purpose of this study was to investigate drinking habits, including sex differences and associations with emotional and behavioral problems.
Color poster with text, graphs, and tables.
Keywords: Posters; Sex differences; College students--Wisconsin--Eau Claire; Binge drinking; Risky behavior; Emotional effects